Validity of choice of court agreements, abusive terms in air carriage contracts, assignments and compensation, is there room for anyone else? (Comments on CJEU Judgment Delayfix, c-519/19) - Ruiz Martín, Anna María (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
In Delayfix case, the Court of Justice of the European Union (CJEU) has interpreted the formal and substantive validity of a “choice of court agreement” included in an air carriage of passenger’s contract. But, for the first time, the CJEU has openly declared the unfair nature of these choice of court agreements, not only for the passengers, but also for third parties assigned by them. In opposition with former case law on the effects of a choice of court agreement for assignees. In carriage of passengers’ contracts, third parties are usually agencies devoted to the defense of air passenger rights and collection of credits who claim for the compensation rights in accordance with the rights conferred by Regulation 261/2004. From the EU Private International Law approach, the preliminary ruling is of interest, being the Brussels I bis regulation the instrument for clarifying whether this choice of court agreement should be deemed as enforceable or not, regarding the requirements of Article 25 Brussels I bis due to these contracts are not considered as consumer contracts. To the analysis of the merits and substantive law, contrarily than under EU Private International law rules these contracts are considered as Business to consumer (B2C) contracts, and Directive 93/13/CEE and other EU Consumer rules must be applied so as to determine the unfair nature of these clauses in these contracts.
Keywords: B2C contracts; passenger; consumer; professional; assignment; passengers’ rights; choice of court agreements; consent; substantial validi; lex fori prorrogatio; renvoi; air carriage contracts; weaker party; abusive terms; assignee; Brussels I bis regulation; Regulation 261/2004; Directive 93/13; asymmetric clauses